Peranan Bimbingan Keagamaan dalam Mengatasi Perilaku Homoseksual (Gay) pada Remaja - Sidik Wahyudin; Neni Noviza (Journal of Society Counseling, 2025)
This study examines the role of religious guidance (bimbingan keagamaan) in addressing homosexual (gay) behavior among adolescents, with a focus on a case study of client “M” in Sukajadi Subdistrict, Banyuasin Regency. Homosexual behavior involves sexual attraction toward individuals of the same sex, which is prohibited in Islamic teachings. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. Data analysis techniques included pattern matching, explanation building, and time-series analysis. The findings reveal that homosexual behavior in client “M” was manifested across four aspects: eye contact, fragrance usage, style of dress, and hairstyle. Religious guidance was implemented over five sessions using the advisory (nasihat) method, structured across three stages: the initial stage, the working/middle stage, and the final stage. Through this guidance, client “M” gradually disengaged from homosexual behavior and began engaging in Islamic practices such as the five daily prayers (shalat), reciting the Qur’an, and dhikr (remembrance of Allah SWT). This study demonstrates that integrating religious values into counseling is effective in promoting behavioral change among adolescents exhibiting sexual deviancy.